2019
DOI: 10.1364/optica.6.001342
|View full text |Cite|
|
Sign up to set email alerts
|

Photonic integrated circuits with bound states in the continuum

Abstract: Waves that are perfectly confined in the continuous spectrum of radiating waves without interaction with them are known as bound states in the continuum (BICs). Despite recent discoveries of BICs in nanophotonics, full routing and control of BICs are yet to be explored. Here, we experimentally demonstrate BICs in a fundamentally new photonic architecture by patterning a low-refractive-index material on a high-refractive-index substrate, where dissipation to the substrate continuum is eliminated by engineering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(79 citation statements)
references
References 37 publications
(39 reference statements)
0
79
0
Order By: Relevance
“…When k y d = 2m, an F-P resonance occurs for transverse magnetic (TM) modes, where k y is the wave vector of the y component of the TM modes, matching that of the TE modes; d is the thickness of the lowrefractive-index film; and m is an integer. According to (28,29), the loss  of the TM mode is inversely proportional to the attenuation length, which we can express as…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When k y d = 2m, an F-P resonance occurs for transverse magnetic (TM) modes, where k y is the wave vector of the y component of the TM modes, matching that of the TE modes; d is the thickness of the lowrefractive-index film; and m is an integer. According to (28,29), the loss  of the TM mode is inversely proportional to the attenuation length, which we can express as…”
Section: Discussionmentioning
confidence: 99%
“…Most of the realized photonic BICs occurred in the conventional architecture of a highrefractive-index material surrounded by a low-refractive environment. Recently, researchers theoretically (28) and experimentally (29) demonstrated that photonic BICs existed in low-refractive-index materials on high-refractive-index substrates. In these low-refractive-index/ high-refractive-index hybrid structures, optical dissipation is prohibited because of the destructive interference of various dissipative channels under certain geometric parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[ 58 ] The Q ‐factor is found to be proportional to α −2 , where α is the asymmetry‐factor of the structure. More recently, BIC was also demonstrated in the hybrid plasmonic–photonic system, [ 59 ] integrated photonic circuit [ 60 ] and zero index material. [ 61 ]…”
Section: Bound States In the Continuummentioning
confidence: 99%
“…This concept was first proposed by von Neumann and Wigner in 1929 1 with a mathematically constructed three-dimensional potential that can support perfectly confined states in a continuous band. Recently, advancement in nanofabrication technologies has triggered fast development of BICs in photonics [10][11][12][13][14][15][16] , and the demonstrated physical phenomena are being applied to the areas of sensors 17,18 , lasers 11 , filters 19 , and integrated photonics 14,15,[20][21][22][23] . For integrated photonics, resonances can be found in a single rib waveguide without any cavity structure due to the BIC mechanism [21][22][23] .…”
mentioning
confidence: 99%
“…For integrated photonics, resonances can be found in a single rib waveguide without any cavity structure due to the BIC mechanism [21][22][23] . In addition, BICs on an integrated photonic platform can be harnessed for realizing low-loss waveguiding by patterning a low-refractiveindex material on a high-refractive-index substrate 14,15,20 . Light guided by the low-refractive-index waveguide can be perfectly confined to the region of high-refractive-index substrate under the low-refractive-index waveguide.…”
mentioning
confidence: 99%